Taxonomic notes on the genus Hymenopyramis (Lamiaceae) in Thailand with one new species, four lectotypifications and two new synonyms - Bongcheewin, Bhanubong; Paton, Alan (Thai Forest Bulletin (Botany), 2024)
Hymenopyramis sabuletorum, a new species from the sandstone plateau in Pha Taem National Park, Ubon Ratchathani Province, Thailand is described and illustrated. Four species are lectotypified, i.e. H. acuminata, H. cana, H. siamensis and H. vesiculosa. Hymenopyramis parviflora var. nitida and H. pubescens are placed in synonymy of H. parviflora and H. siamensis, respectively. A key to the seven species recognised in Thailand is provided.